Evaluation of attitudes of patients regarding vaccine hesitancy during COVID-19: community pharmacy setting - RABUŞ, ŞULE (My University, 2022)
Background and Objective: Vaccine hesitancy leads to decreases in vaccination rates and causes an increase in preventable epidemics and diseases. The aim of this study is to evaluate the attitudes of patients applying to a community pharmacy regarding vaccine hesitancy during COVID-19. Setting and Method: This study was conducted in one community pharmacy for any reason between September and December 2021, Istanbul, Turkey. The ‘‘Scale of Vaccine Hesitancy’’ (1) (consisted of 12-items) was applied to the patients face to face. Sociodemographic characteristics of the patients were recorded. The results of the questionnaire were calculated according to the scale guideline. The higher score represents the higher vaccine hesitancy. Main outcome measures: Scores obtained from the scale of vaccine hesitancy and correlation of the scores with patients’ parameters such as chronical diseases, Covid-19 disease and vaccination history. Results: Of the 43 patients 90% were female. The mean age was 37.5. Thirty-five percent of the participants had COVID-19 and 69.8% had a family history of COVID-19. About 79.1% have had the COVID-19 vaccine and 76% of those were vaccinated with BioNTech and the rest with Sinovac. The mean of the vaccine hesitancy score was calculated as 27.4 (min 12-max 50). Vaccine hesitancy score was higher for patients who were not vaccinated than who were vaccinated (41.0 vs 24.2; p \0.001). The vaccine hesitancy score was higher in patients with chronic disease (28.1), in chronic medication users (28.8), in those who had COVID-19 history (29.5), and those with a family history of COVID-19 (28.2). Cronbach alpha value of the scale is 0.846. Conclusion: It was determined that unvaccinated patients had higher vaccine hesitancy scores. In addition, vaccine hesitancy score was higher in the patients with chronic disease and who had COVID-19. It is very important to have a high rate of vaccination, especially in a pandemic or life-threatening disease. Therefore, educating and relieving patients can be an important step in overcoming this problem. As pharmacists, the closest position to patients, we have a great responsibility in order to change the perspective on vaccination. References: 1. Kılınc¸arslan MG, Sarıgu¨l B, Toraman C¸, S¸ ahin EM. Development of valid and reliable Scale of Vaccine Hesitancy in Turkish language. Konuralp Medical Journal. 2020;12(3):420–429. doi: 10. 18521/ktd.693711 Disclosure of Interest: None Declared.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides